Misoprostol treatment vs expectant management in women with early non‐viable pregnancy and vaginal bleeding: a pragmatic randomized controlled trial. (5th December 2017) - Fernlund, A.; Jokubkiene, L.; Sladkevicius, P.; Valentin, L.
ABSTRACT: Objective: To compare vaginal misoprostol treatment with expectant management in early non‐viable pregnancy with vaginal bleeding with regard to complete evacuation of the uterine cavity within 10 days after randomization. Methods: This was a parallel randomized controlled, open‐label trial conducted in Skåne University Hospital, Sweden. Patients with anembryonic pregnancy or early fetal demise (crown–rump length ≤ 33 mm) and vaginal bleeding were randomly allocated to either expectant management or treatment with a single dose of 800 μ g misoprostol administered vaginally. Patients were evaluated clinically and by ultrasound until complete evacuation of the uterus was achieved (no gestational sac in the uterine cavity and maximum anteroposterior diameter of the intracavitary contents < 15 mm as measured by transvaginal ultrasound on midsagittal view). Follow‐up visits were planned at 10, 17, 24 and 31 days. Dilatation and evacuation (D&E) was recommended if miscarriage was not complete within 31 days, but was performed earlier at patient's request, or if there was excessive bleeding as judged clinically. Analysis was by intention to treat. The main outcome measure was number of patients with complete miscarriage without D&E ≤ 10 days. Results: Ninety‐four patients were randomized to misoprostol treatment and 95 to expectant management. After exclusion of three patients and withdrawal of consent by two patients in the expectant management group, 90 women were included in this group. Miscarriage was complete ≤ 10 days in 62/94 (66%) of the patients in the misoprostol group and in 39/90 (43%) of those in the group managed expectantly (risk difference (RD) = 23%; 95% CI, 8–37%). At 31 days, the corresponding figures were 81/94 (86%) and 55/90 (61%) (RD = 25%; 95% CI, 12–38%). Two patients from each group underwent emergency D&E because of excessive bleeding and one of these in each group received blood transfusion. The number of patients undergoing D&E at their own request was higher in the expectantly managed group, 15/90 (17%) vs 3/94 (3%) in the misoprostol group (RD = 14%; 95% CI, 4–23%), as was the number of patients making out‐of‐protocol visits, 50/90 (56%) vs 27/94 (29%) (RD = 27%; 95% CI, 12–40%). Compared with the expectant management group, more patients in the misoprostol group experienced pain (71/77 (92%) vs 91/91 (100%); RD = 8%; 95% CI, 1–17%) and used painkillers (59/77 (77%) vs 85/91 (93%); RD = 17%; 95% CI, 5–29%). No major side effect was reported in any group. Conclusions: In women with early non‐viable pregnancy and vaginal bleeding, misoprostol treatment is more effective than is expectant management for complete evacuation of the uterus. Both methods are safe but misoprostol treatment is associated with more pain than is expectant management. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. This article has been selected for Journal Club. Clickhere to view slides and discussion points.